Analisis Kinerja Keuangan Pada Perusahaan BUMN Subsektor Semen Menggunakan Metode EVA dan MVA Periode Tahun 2020 - 2023 - Triana Nurliawati; Ade Sri Mulyani (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
The world is experiencing a period of recovery due to the aftermath of the pandemic, several companies have carried out various strategies to ensure performance is going well. Based on financial data listed on the IDX, the growth of the cement industry in Indonesia has the opportunity to grow accompanied by soaring market demand for both private and government infrastructure development. With this research, it is useful to know the calculation of financial performance through financial statement analysis. This research uses non-statistical quantitative methods. The secondary data source is the financial statements of cement subsector BUMN companies using the EVA and MVA methods which can be accessed through the official IDX and company websites. Sampling using purposive sampling method that uses several criteria. The results of the calculation of EVA three companies in 2020 - 2023 in a row are positive, which means that adding value to the company's capital costs results in an income figure above zero in other words there is no minus. While the results of the calculation of two companies in 2022 are negative, which means that they do not add value to the company's capital costs, resulting in income below zero, in other words, minus. The results of the calculation of MVA in all cement sub-sector companies in 2020 - 2023 are positive, which means that adding value to the company's shares results in an income figure above zero, in other words, there is no minus